1991
DOI: 10.1055/s-0038-1646420
|View full text |Cite
|
Sign up to set email alerts
|

LY53857, a 5HT2 Receptor Antagonist, Delays Occlusion and Inhibits Platelet Aggregation in a Rabbit Model of Carotid Artery Occlusion

Abstract: SummaryThe present study was designed to evaluate the effectiveness of the ergoline 5HT2 receptor antagonist, LY53857 in a rabbit model of vascular arterial occlusion. LY53857 (1 and 10 εM) inhibited serotonin amplified platelet aggregation responses to threshold concentrations of ADP in rabbit platelets in vitro. LY53857 (1 εM) not only inhibited the serotonin component of rabbit platelet aggregation, but also inhibited in vitro aggregation induced by ADP (48.7 ± 16.7% inhibition), collagen (76.1 ± 15.9% inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Most importantly, the desisopropyl metabolites of LY215840 and amesergide also inhibited serotonin-amplified ADP-induced rabbit platelet aggregation in vitro. Interestingly, the concentrations required to inhibit serotonin-amplified ADP-induced aggregation for these ergolines were higher than predicted by their 5-HT, receptor binding affinities, but similar to the concentrations of other 5-HT2 receptor antagonists required to inhibit platelet aggregation in previous studies [ McBride et al, 1987[ McBride et al, , 1990Wilson et al, 1991;Cohen et al, 19921. The lower sensitivity of the functional assay of 5-HT amplified platelet aggregation to inhibition may be related to the p M concentration of 5-HT required to induce the amplification or to other factors.…”
Section: Disc U Sslonsupporting
confidence: 79%
See 2 more Smart Citations
“…Most importantly, the desisopropyl metabolites of LY215840 and amesergide also inhibited serotonin-amplified ADP-induced rabbit platelet aggregation in vitro. Interestingly, the concentrations required to inhibit serotonin-amplified ADP-induced aggregation for these ergolines were higher than predicted by their 5-HT, receptor binding affinities, but similar to the concentrations of other 5-HT2 receptor antagonists required to inhibit platelet aggregation in previous studies [ McBride et al, 1987[ McBride et al, , 1990Wilson et al, 1991;Cohen et al, 19921. The lower sensitivity of the functional assay of 5-HT amplified platelet aggregation to inhibition may be related to the p M concentration of 5-HT required to induce the amplification or to other factors.…”
Section: Disc U Sslonsupporting
confidence: 79%
“…Because these agents may have clinical utility in thrombosis [Cushing et al, 19933, it became important to establish their comparative efficacy in blocking platelet 5-HT, receptors as well as vascular 5-HT2 receptors. Furthermore, because antithrombotic activity is readily documented in the rabbit for such agents [Wilson et al, 1991;Cohen et al, 19921, we utilized rabbit platelet receptors which are known to possess 5-HT, receptors [Wilson et al, 1991;Cohen et al, 19921. Both [ Wilson et al, 19911 have shown marked efficacy in rabbit models of thrombosis. The marked efficacy of 5-HT, receptor antagonists in rabbit models of thrombosis may be related in part, to the relative importance of serotonin in mediating platelet aggregation responses in the rabbit [Killam et al, 19911 although other factors may also contribute [Cushing et al, 19931.…”
Section: Disc U Sslonmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in thrombosis models have described the ability of various 5-HT2 receptor antagonists to inhibit coronary cyclic flow variations in the dog (3,4,5) , to extend the time of (6) or inhibit thrombus formation in various thrombosis models in the rat (7). As a potential therapy for vascular occlusive disease, ketanserin has been clinically studied and has been shown to reduce the incidence of primary (myocardial infarction, stroke or death) and secondary (angina, deep vein thrombosis, transient ischemic attacks) events in a subgroup of patients with intermittent claudication (8).…”
mentioning
confidence: 99%
“…When platelets are activated during the formation of (for example) a haemostatic plug, they release adenine nucleotides (mainly ADP) and 5-hydroxytryptamine (5-HT) from storage ␣-granules, which in turn amplify the aggregatory response, the latter via its effects on platelet 5-HT 2A receptors (5)(6)(7)(8). Indeed, several 5-HT 2 receptor antagonists have been shown to inhibit 5-HT-induced platelet aggregation and arterial thrombosis in animal models (9)(10)(11)(12)(13)(14)(15)(16)(17). In addition, platelet-derived 5-HT would contribute to vasoconstriction at the site of platelet-rich thrombus formation due to its effects on 5-HT 2A , 5-HT 1B and 5-HT 1D receptors according to the vascular bed, and the functional status of the endothelium (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%